A Century of Hypomethylating Agent: A Remarkable Response to Azacitidine Monotherapy for Relapsed Acute Myeloid Leukemia – A Case Report - Chetan Jeurkar; Amry Majeed; Lindsay Wilde; Gina Keiffer; Margaret Kasner (Case Reports in Oncology)
Introduction: Acute myeloid leukemia (AML) is a disease of the elderly with a median age at diagnosis of 68 and with a very poor prognosis outside of those patients who have cytogenetic and/or molecular findings which confer a better prognosis. Most fit patients are treated with chemotherapy and then allogeneic hematopoietic stem cell transplant if they are intermediate or poor risk by ELN 2022 criteria (aSCT). aSCT is the mainstay of curative treatment although many patients are not candidates due to age, performance status, and comorbidities. In patients who are not candidates for curative treatment, low-intensity chemotherapy regimens, including monotherapy with hypomethylating agents (HMAs) such as azacitidine or decitabine, may be trialed with a palliative intent. In patients who have relapsed disease, responses to therapy are generally dismal and overall survival is extremely low. Case Presentation: We report a 73-year-old male patient who was initially diagnosed with inversion 16 AML, underwent induction chemotherapy with 7 + 3 and then consolidation with 4 cycles of high-dose cytarabine. He was found to have relapse after consolidation but did not elect to undergo allogeneic bone marrow transplant and so was given palliative single-agent azacitidine. He has since received over 100 cycles of azacitidine and remains in remission. Conclusion: To our knowledge, no other reports describe relapsed AML treated with HMA monotherapy achieving such exceptional survival. The remarkable response duration suggests mechanisms beyond cytotoxicity. Further research should explore HMA monotherapy’s effects across AML subgroups, including inv(16).